2023
DOI: 10.3390/w15010186
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Optimization of Rainwater Harvesting Systems Based on a Cost–Benefit Analysis: A Financial Support Program Review and Parametric Sensitivity Analysis

Abstract: Water risk has been continuously rising due to climate change and ownership disputes of water resources. Dam construction to secure water resources may lead to environmental problems and upstream immersion. On the other hand, rainwater harvesting systems can effectively supply water at a low cost, although economic efficiency of these systems is still debatable. This study evaluates financial support programs to promote installation of rainwater harvesting systems, increasing economic feasibility. Based on a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The same findings were reported for residential rainwater harvesting systems in Austin, Texas, USA, where studied RWH systems would be not profitable without financial support [80]. A recent paper by Jin et al [81] underlines that national and financial policies promoting rainwater harvesting systems should be available to ensure the economic profitability of these systems and to increase the acceptance of the potential investors and their users' willingness-to-pay. The required community acceptance for rainwater harvesting designs, highly related to the economic issues of such systems, was also underlined as a social aspect of sustainable rainwater management [82].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The same findings were reported for residential rainwater harvesting systems in Austin, Texas, USA, where studied RWH systems would be not profitable without financial support [80]. A recent paper by Jin et al [81] underlines that national and financial policies promoting rainwater harvesting systems should be available to ensure the economic profitability of these systems and to increase the acceptance of the potential investors and their users' willingness-to-pay. The required community acceptance for rainwater harvesting designs, highly related to the economic issues of such systems, was also underlined as a social aspect of sustainable rainwater management [82].…”
Section: Discussionsupporting
confidence: 53%
“…The degree of implementation of LID systems varies significantly between different countries all over the world [68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. The use of low-impact solutions very often requires additional investment and/or operating costs compared to conventional designs, which may be one of the factors affecting the limited application of these systems.…”
Section: Low-impact Development In Urbanized Catchmentsmentioning
confidence: 99%
“…The current state of the art and future perspectives for rainwater harvesting systems in Europe were presented in the paper by Wartalska et al [10], whereas Dalman et al [11] and Jin et al [12] showed the costs and benefits of this subject. On the other hand, de Sá Silva et al [13] presented a review of the environmental, economic, and social aspects of the use of the rainwater harvesting systems.…”
Section: Introductionmentioning
confidence: 99%
“…Rainwater harvesting (RWH) systems offer a practical way to mitigate water stress. RWH systems provide direct runoff containment while simultaneously storing water, which can then be used for irrigation [Jin et al 2023]. Rainwater harvesting takes attention by individual builgings from the roof top or gardens for individual use.…”
Section: Introductionmentioning
confidence: 99%